2011
DOI: 10.1038/eye.2011.239
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour efficacy with the dorzolamide/timolol-fixed combination compared with the brimonidine/timolol-fixed combination in primary open-angle glaucoma

Abstract: Aim The aim of this study is to compare the 24-hour efficacy of dorzolamide/timolol-fixed combination (DTFC) and brimonidine/ timolol-fixed combination (BTFC) in primary open-angle glaucoma (POAG). Methods One eye each of 77 POAG patients was included in this prospective, observer-masked, crossover comparison. Following a 2-month timolol run-in period, patients had three intraocular pressure (IOP) measurements at 1000, 1200 and 1400 h while on timolol treatment. Patients showing at least a 20% IOP reduction on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Some other fixed-combination glaucoma medications have also demonstrated 24-hour control of IOP. For example, fixed combinations of dorzolamide and timolol, and brimonidine and timolol both significantly decrease IOP from baseline (mean IOP reduction: 2.9 mmHg and 2.2 mmHg, respectively) 59. However, IOP reductions were greater during the night (6 pm and 2 am) with dorzolamide and timolol compared with brimonidine and timolol, which was to be expected given the decreased evening efficacy of both components 58,59.…”
Section: Efficacy Of Bbfcmentioning
confidence: 86%
See 1 more Smart Citation
“…Some other fixed-combination glaucoma medications have also demonstrated 24-hour control of IOP. For example, fixed combinations of dorzolamide and timolol, and brimonidine and timolol both significantly decrease IOP from baseline (mean IOP reduction: 2.9 mmHg and 2.2 mmHg, respectively) 59. However, IOP reductions were greater during the night (6 pm and 2 am) with dorzolamide and timolol compared with brimonidine and timolol, which was to be expected given the decreased evening efficacy of both components 58,59.…”
Section: Efficacy Of Bbfcmentioning
confidence: 86%
“…For example, fixed combinations of dorzolamide and timolol, and brimonidine and timolol both significantly decrease IOP from baseline (mean IOP reduction: 2.9 mmHg and 2.2 mmHg, respectively) 59. However, IOP reductions were greater during the night (6 pm and 2 am) with dorzolamide and timolol compared with brimonidine and timolol, which was to be expected given the decreased evening efficacy of both components 58,59. Given that significant IOP reductions with BBFC are still seen at 8 am (10 hours after dosing), it is likely that the nocturnal IOP-lowering efficacy of BBFC is being conferred by the brinzolamide, not the brimonidine, component 60,61.…”
Section: Efficacy Of Bbfcmentioning
confidence: 99%
“…DTFC exerts better e cacy than any single medication. Studies suggested that DTFC could help decrease IOP signi cantly in patients with POAG [23][24][25][26][27][28][29][30][31]. However, no systematic review has investigated the e cacy and safety of DTFC in treating POAG.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…It had also been suggested that DTFC may provide better 24-hour efficacy than brimonidine/timolol fixed combination (BTFC) in primary open-angle glaucoma (POAG) [120]. …”
Section: Contemporary Pharmacological Management Of Glaucomamentioning
confidence: 99%